Dinamika Sifat Kimia Tanah dan Perlakuan Pupuk Bokashi Kombinasi Kotoran Kuda dan Sekam Padi - Alan, Silvester Umbu; Jawang, Uska Peku (Jurnal Agroteknologi (Agronu), 2024)
Plant productivity is determined by the availability or quality of growing media for plants. Soil as a growing medium for plants needs to be considered for the availability of nutrients to support plant growth and development. The soil of each region has its own characteristics, because it is determined by the formation process. One way to improve soil quality is by providing organic matter. Organic materials available in the environment are livestock manure and rice husk. The purpose of this study was to determine the effect of bokashi fertilizer from a combination of horse manure and rice husk on the dynamics of soil chemical properties. This research was conducted from March - May 2024 located in the field laboratory of Wira Wacana Sumba Christian University and laboratory tests at the Soil Chemistry Laboratory of Nusa Cendana University. Materials for making bokashi fertilizer were obtained from farmers and rice mills in Matawai Village. The method used in this study was an experimental method with a complete randomized design, with four treatments and repeated four times, so that the number of observations consisted of 16 observation units. One treatment with four doses of bokashi fertilizer treatment with a combination of horse manure and rice husk, namely P0: control, P1: 5 ton ha-1, P2: 10 ton ha-1, and P3: 15 ton ha-1. The treatment results showed an increasing effect on soil chemical properties, namely pH, c-organic, N-total, P2O5, and CEC. The 15 ton ha-1 treatment gave the highest value of soil chemical properties.